1988
DOI: 10.1111/j.1365-2109.1988.tb00432.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of feeding level on growth rate of Tilapia aureus (Steindachner) reared in a closed circulated system

Abstract: Abstract. Four populations of 42 specimens (mean initial b.wt 64·02–65·29g) of Tilapia aureus (Steindachner), were reared for 15 weeks in 600‐1‐capacily cylindrical plastic tunks, from a closed circulated system, al four feeding levels (1,2,3 and 4% of b.wt daily). A feeding level of 2% of b.wt daily seems to be the best, taking into consideration biological (specific growth rale, food conversion rate, protein efficiency ratio, values of total plasma lipids, cholesterol and triglyceridcs. haematocrit, proxima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
14
0
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 14 publications
5
14
0
1
Order By: Relevance
“…The optimal daily feeding rates of 2% or 3% for larger silver perch (50^500 g) at temperatures over 20 1C are similar to those reported for many other cultured species (De Silva et al1986;Merola & de Souza 1988;Papoutsoglou & Voutsinos 1988;Hung et al 1989;Lovell 1989a, b;Jodun 2004). Feeding rates are temperature dependent, and optimal rates for silver perch below 20 1C were 0.5% and 1% (Table 4).…”
Section: Feeding Rates and Frequenciessupporting
confidence: 81%
See 1 more Smart Citation
“…The optimal daily feeding rates of 2% or 3% for larger silver perch (50^500 g) at temperatures over 20 1C are similar to those reported for many other cultured species (De Silva et al1986;Merola & de Souza 1988;Papoutsoglou & Voutsinos 1988;Hung et al 1989;Lovell 1989a, b;Jodun 2004). Feeding rates are temperature dependent, and optimal rates for silver perch below 20 1C were 0.5% and 1% (Table 4).…”
Section: Feeding Rates and Frequenciessupporting
confidence: 81%
“…An asymptotic relationship between ration size and growth has been reported in many other species (Brett, Shelbourne & Shoop 1969;Papoutsoglou & Voutsinos 1988;Hung, Lutes, Conte & Storebakken 1989;Qin & Fast 1996;Adebayo, Balogun & Fagbenro 2000). An asymptotic relationship between ration size and growth has been reported in many other species (Brett, Shelbourne & Shoop 1969;Papoutsoglou & Voutsinos 1988;Hung, Lutes, Conte & Storebakken 1989;Qin & Fast 1996;Adebayo, Balogun & Fagbenro 2000).…”
Section: Feeding Rates and Frequenciesmentioning
confidence: 67%
“…) in blood and liver, indicating a reduction 512 in feed utilization (Papoutsoglou & Voutsinos, 1988;Shimeno et al, 1997). Thus, the blood chemistry and tissues biochemical composition could be used as indexes to explain possible differences in overall results culturing aquatic species together at different densities.…”
Section: Introductionmentioning
confidence: 99%
“…Ellis et al (2002) reviewed more than 40 studies concerning density effects on fish health in rainbow trout, most of them associated fish performance degradation at high density due to fish stress, aggressive interactions and the development of feeding hierarchies (Wallace et al 1988;Baker and Aylers 1990;Pickering 1992;Alanärä and Brännäs 1996). Conversely, other studies reported that very low densities could impact feed intake because of the establishment of hierarchical feeding behaviour (Papoutsoglou et al 1987(Papoutsoglou et al , 1990Pickering et al 1989;Zoccarato et al 1994). Most studies on the density effects on fish welfare do not generally distinguish between specific effects related to biomass increase per se and those caused by the degradation of water quality (Person-Le-Ruyet et al 2008).…”
Section: Introductionmentioning
confidence: 99%